Crop wild relatives—undervalued, underutilized and under threat? - Ford-Lloyd, B.V.; Schmidt, M.; Armstrong, S.J.; Barazani, O.; Engels, J.; Hadas R; Hammer K; Kell, S.P.; Kang D; Khoshbakht K; Li Y; Long C; et al. (Oxford University Press, 2011)
The world's wealth of plant genetic resources has much value for world food security, but these resources are under considerable threat. Crop improvement, particularly under climate change, depends on the genetic diversity of our plant genetic resources, which are arguably inadequately conserved and poorly used. There is wide recognition that the Convention on Biological Diversity's 2010 targets to reduce the loss of biodiversity have not been met. Biodiversity is at risk from multiple threats, including climate change, and the genetic diversity contained within plant genetic resources, particularly of species that are wild relatives of our crops, faces similar threats but is essential to our ability to respond to the new stresses in the agricultural environment resulting from climate change. It is important to consider the genetic value of these crop wild relatives, how they may be conserved, and what new technologies can be implemented to enhance their use.